Screening of the bio-decolorization ability of synthetic dyes and the degradation of hydrocarbon bacteria Serratia marcescens MBC1 - Achmad Arifiyanto; Berliana Damayanti; Meishy Handerlin Putri; Cindy Lukita Ratih Riyanto (Biogenesis: Jurnal Ilmiah Biologi, 2022)
Humans are inseparable from using hydrocarbons, including fossil fuels, dyes, and oleochemical products. This has frequently resulted in a high possibility of waste spills polluting the environment. A biological approach using microbes was used to facilitate many of these countermeasures. This study aimed to determine the ability of the bacterium Serratia marcescens MBC 1 isolate as a biodegradation agent for various hydrocarbons and a bio-decolorizing agent for synthetic dyes. The bacterial growth media used were solid and tryptic soy broth. Methylene blue, congo red, methyl red, methyl orange, and crystal violet were synthetic dyes at a concentration per million. Within 7 days, several synthetic dyes tested showed decolorization. Methylene blue has the fastest decolorization time, taking just 24 h. The lipase index method was used to assess the propensity of hydrocarbons to degrade qualitatively. Kerosene had the highest lipolytic index at 6.31, followed by used cooking oil at 5.48 index, used lubricant at 5.37 and diesel at 3.63 index. Quantitative and comprehensive in-depth testing of the potential achievements of this initial test will be used in solving environmental problems that may occur further, especially related to the impact of the use of synthetic dyes.